Effect of Operational Parameters on a Novel Combined Cycle of Ejector Refrigeration Cycle and Kalina Cycle - SEÇKİN, CANDENİZ (ASME, 2020)
A Kalina cycle is coupled to an ejector refrigeration cycle to generate power and refrigeration outputs, simultaneously. Ejector refrigeration cycle is driven by the heat which is extracted from a high-temperature/pressure stream of Kalina cycle working fluid since the energy content of this fluid stream is not directly utilized in power production in the Kalina cycle. Supplied heat to the proposed combined cycle is produced by combustion of biomethane which is obtained from anaerobic digestion of biomass, namely, food waste. System reactions to altering operation conditions (entrainment ratio, condenser pressure, evaporator pressure, and superheating degree) in terms of refrigeration production, power production, energy efficiency, exergy efficiency, and exergy of produced power and refrigeration are analyzed. The results are reported for R290, R134a, and R152a working fluids of the ejector refrigeration cycle and an extensive discussion of the results are provided. It is shown that the entrainment ratio strongly affects the thermal and exergy efficiency results. The highest thermal and exergy efficiency results are performed when R290 and R134a are used, whereas the lowest thermal and exergy efficiencies are obtained when R152a and R290 are used as the refrigerant, respectively.
Keywords: cogeneration; power; refrigeration; ejector refrigeration cycle; Kalina cycle; energy conversion/systems; energy from biomass; energy systems analysis; WASTE HEAT-RECOVERY; THERMODYNAMIC ANALYSIS; ANAEROBIC-DIGESTION; ORGANIC RANKINE; POWER-SYSTEM; EXERGOECONOMIC ANALYSIS; ENVIRONMENTAL-ANALYSIS; COGENERATION SYSTEM; CASCADE UTILIZATION; COOLING-SYSTEM